Salzmann’s Nodular Degeneration - S. V. Trufanov; I. A. Riks; M. Ezugbaya (Oftalʹmologiâ)
Saltzman’s nodular degeneration is a rare, non-inflammatory, slowly progressive degenerative disease of the cornea characterized by bluish-white nodules elevated above the surface of the cornea. More often nodules are located in the mid periphery of the cornea, they can spread into the optical zone. Sometimes localize along the limbus. They consist of dense heterogeneous collagen tissue with hyalinization, localized between the epithelium and Bowman’s layer. Can penetrate deeper into the stroma. The exact pathophysiological mechanism of the lesion is unclear. It is considered that this condition is associated with a violation of the structural relationship of epithelial cells against the background of chronic inflammation of the ocular surface, which leads to the destruction of the Bowman’s layer, the activation and migration of fibroblasts anteriorly, and the deposition of a disorganized extracellular matrix in subepithelial nodules. Clinically, the disease can be manifested by irritation and inflammation of the ocular surface, dryness or decreased vision, more often due to flattening of the cornea and astigmatism. In some cases, the formed tissue can be easily separated from the corneal surface, leaving Bowman’s layer almost intact. In this case, a subsequent phototherapeutic keratectomy may be required to “smooth” the surface. Relapses in these eyes are rare. In other situations (often with extensive peripheral vascularization), the lesions involve the anterior stroma, making it more difficult to remove them while maintaining the smoothness of the cornea. Several laser ablation procedures may be required, but there is a high risk of recurrence with this approach. It may be necessary to treat the meibomian gland’ dysfunction and dry eye syndrome that often accompanies Saltzman’s degeneration to reduce the risk of disease progression.